Carotid endarterectomy unexpectedly resulted in optimal blood pressure control - Kirin, Ivan, liječnik (Array, 2009)
Abstract: Resistant hypertension is defined as hypertension that remains above 140/90 mmHg despite the provision of three or more antihypertensive drugs in a rational combination at full doses and including a diuretic. It is associated with adverse clinical outcome and therefore requires aggressive medical treatment. We present a case of 70-year-old woman who was treated for resistant hypertension with a diuretic, ACE-inhibitor, calcium channel blocker, and with centrally acting antihypertensive, moxonodine. Despite of aggressive medical treatment her blood pressure remained above 160/90 mmHg continuously. Large diagnostic workup excluded common causes of secondary hypertension, but revealed significant carotid stenosis present on left internal carotid artery. Carotid endarterectomy was performed in order to improve cerebrovascular prognosis, but unexpectedly resulted in optimal control of her blood pressure. Two months after operation patient was on only one antihypertensive drug, having blood pressure below 130/85 mmHg. We suggest that in selected patients resistant hypertension could be associated with carotid stenosis and carotid sinus baroreceptor dysfunction. For definite conclusions further studies are warranted